KHI's Perspective on the Legality of Adoption by Single Parents - Farhah Intan Sari Haras (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the legal status of single parents in adopting children within the framework of the Compilation of Islamic Law (KHI) in Indonesia. The research aims to analyze whether the adoption carried out by a single parent is legally permissible according to Islamic family law and how KHI accommodates such practices in the context of child protection. Using a normative juridical method through statutory, conceptual, and case approach, this study reviews Islamic legal principles on kafalah, lineage, guardianship, and the obligation to prioritize the best interests of the child. Data were obtained through literature review of Islamic jurisprudence, national regulations on child protection, and relevant decisions of the Religious Courts. The findings indicate that Islamic law does not prohibit single-parent adoption as long as the child’s lineage remains unchanged and the welfare of the child is ensured. KHI provides general guidelines on adoption but does noSt explicitly restrict adoption based on marital status, thereby allowing judges to use judicial reasoning grounded in maslahah to assess the eligibility of single parents. The study concludes that the absence of detailed technical rules in KHI contributes to variations in judicial interpretation, emphasizing the need for clearer legal guidelines to ensure consistency, legal certainty, and stronger child protection in adoption practices involving single parents.